Large Eddy Simulation of Gas Diffusion Process in Open Space under Wind Effect - Song, Meijiao; Sun, Xu; Li, Wenxin; Tang, Huang; Liu, Zicheng; Jiang, Wanfei; Zhang, Jingmin; Tang, Wei; Wen, Kai (Journal of Environmental Accounting and Management, 2026)
In this paper, the large eddy simulation (LES) method is applied to gas diffusion process in open space under wind effect. Firstly, the governing equations of gas diffusion employed in LES are introduced, and the corresponding solution procedure is discussed. Subsequently, using LES with DSM subgrid-scale model, the diffusion process of the methane discharging from a chimney under wind effect is simulated, and the lateral and vertical distribution patterns of methane concentration in the wake of the chimney are compared with the experimental results, to examine the accuracy and stability of LES in simulating the diffusion process of light gas in open space. Finally, using the full-scale experimental results concerning diffusion of the mixture gas of nitrogen and Freon-12, the accuracy of LES in simulating heavy gas diffusion is examined, and the advantage of LES over Reynolds-averaged Navier-Stokes (RANS) method in computing the unsteady gas diffusion process is examined. For both cases considering light gas and heavy gas, the numerical results from LES show very good agreement with the experimental results, indicating its potential in simulating the gas discharging or leakage process in various industrial applications.